Newborn Infanticide within Hospital Premise An Unusual Case Report - Haridas, S V; Patekar, M B; Ninal, N S; Zine , K U (Journal of Indian Academy of Forensic Medicine, 2014)
Many a time’s forensic pathologists come across infant deaths. Neonaticide is the deliberate killing of a child within four weeks of birth. Infanticide is the killing of a child who is less than one year of age. The killing of newborn infants has been practiced from time immemorial for a variety of reasons. Today, the social stigma attached to the out-of-wedlock pregnancy is usually the most common motivating factor to resort to the commission of such a crime. Infanticide can be performed by the acts of commission or acts of omission. Acts of commission include strangulation, smothering, blunt head injury, multiple injuries, drowning and poisoning. In infant strangulation deaths, the classical features of asphyxia are often absent, presumably because of the ease with which the vulnerable infant dies. Infant death is a challenge to forensic pathologist and to law enforcement authorities. Here we present an unusual case of male newborn infanticide by ligature strangulation while he was along with his mother in postnatal ward.